USE OF REAL-TIME qRT-PCR FOR FMD VIRUS DETECTION IN CATTLE MILK - A. M. Timina; S. N. Fomina; Т. К. Mayorova (Ветеринария сегодня)
FMDV can be shed with milk of infected animals and infect susceptible animals. The possibility of using real-time qRT-PCR for FMD virus detection in cattle milk was assessed. To prepare samples of FMDV infected milk the following strains were used: А No. 2177/ Amursky/2013, О No. 2123/South Ossetia/2011, Asia-1 No. 1987/Amursky/2005, С No. 564, SAT-1 No. 2033/Botswana, SAT-2/Saudi Arabia, SAT-3/Bech 1/65. For specifcity test swine vesicular disease O-72 strain, Vesicular Exanthema of Swine A-48 strain and vesicular stomatitis virus Indiana strain from FGBI “ARRIAH” collection were used. The obtained data showed that real time qRT-PCR can be successfully used for the virus detection in milk of infected cows as well as in epithelium and cell cultures. Analytical sensitivity of real-time qRT-PCR in milk samples is 1–10 TCD50/ml, the method specifcity is 100%. When identifying basic validation characteristics of the method it was proven that real-time qRT-PCR demonstrates precision and sensitivity and can detect FMDV in its genetic diversity. So, the detected data showed that the real-time qRT-PCR is a precious method of milk and dairy product control.